2014
DOI: 10.1007/s00210-014-1052-7
|View full text |Cite
|
Sign up to set email alerts
|

Acute hemodynamic effects of angiotensin- converting enzyme inhibition after prolonged cardiac arrest with Bretschneider’s solution

Abstract: Evidence as to how ACE inhibitors attenuate ischemia-reperfusion injury (IR) after cardioplegic arrest remains scarce. Twenty-four rabbit hearts were perfused on a Langendorff apparatus. Control hearts (n = 6) were arrested with pure histidine-tryptophan-ketoglutarate (HTK)-Bretschneider. Treatment groups received added to the cardioplegic solution (n = 6) captopril (100 μmol/l) and losartan (100 μmol/l) for selective AT1-receptor antagonism or BQ123 (100 nmol/l) for selective ETA-receptor antagonism. Pre-isch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
0
8
0
3
Order By: Relevance
“…Therefore, it may be a favourable strategy to inhibit MPT and depolarization of mitochondria . Accordingly, a beneficial effect of MTP‐inhibition by cyclosporine was recently demonstrated by the authors . Moreover, it has been described in liver cells that minocycline protects from ischemia/reperfusion injury by suppressing mitochondrial calcium uptake and inhibiting MPT.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Therefore, it may be a favourable strategy to inhibit MPT and depolarization of mitochondria . Accordingly, a beneficial effect of MTP‐inhibition by cyclosporine was recently demonstrated by the authors . Moreover, it has been described in liver cells that minocycline protects from ischemia/reperfusion injury by suppressing mitochondrial calcium uptake and inhibiting MPT.…”
Section: Discussionmentioning
confidence: 98%
“…33 Accordingly, a beneficial effect of MTP-inhibition by cyclosporine was recently demonstrated by the authors. 34 Moreover, it has been described in liver cells that minocycline protects from ischemia/reperfusion injury by suppressing mitochondrial calcium uptake and inhibiting MPT. This resulted in diminished mitochondrial swelling and in decreased release of pro-apoptotic factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, information regarding the application of ACEIs in patients with CA and resuscitation is limited. Recently, Hoyer et al provided evidence that ACE inhibition led to significantly improved myocardial contractility after prolonged CA with Bretschneider's solution ( 36 ). In line with the findings of this study, our data demonstrated that enalapril also successfully decreased myocardial injury in a swine model of CA-resuscitation.…”
Section: Discussionmentioning
confidence: 99%